Role of Multi Strain Probiotics Recurrent Respiratory Tract Infections - Shoaib, Madiha; Zafar, Sadia; Arfah (Indus Journal of Bioscience Research, 2025)
Background: Pakistan continues to experience a high burden of respiratory tract infections. Unfortunately, research on interventions to minimize RRTIs is scarce, and no definitive strategies have been developed. Probiotics have shown promise in supporting gut health and immune function in young children, according to various clinical studies. However, their potential to prevent or reduce the recurrence of RRTIs is not well-established. Therefore, I intend to undertake this study to assess whether probiotics can be used as a practical approach to reduce the frequency of RRTIs. Objectives: To determine efficacy of role of multi strain probiotics in recurrent respiratory tract infection.  Methodology: This study was conducted at the Department of Pediatrics, Allied Hospital, Faisalabad, Pakistan, during the period of one year, from April, 2024 to April, 2025 and enrolled 95 children meeting the operational criteria for RRTIs. All received a 14-days course of Ecotec® probiotics containing Lactobacillus acidophilus LA-5, Bifidobacterium BB-12, Streptococcus thermophilus STY-31, and Lactobacillus delbrueckii subsp. bulgaricus LBY-27. Participants were followed for six months to assess recurrence. Stratified chi-square analysis was performed. Results: The majority (85.3%) of participants were aged under five. Overall, 56 children (58.9%) showed no recurrence of RRTIs. Breastfeeding showed a significant association with effectiveness (p = 0.048), while age, gender, immunization, nutritional status, and type of infection did not show significant associations (p > 0.05). No adverse effects were reported Conclusion: Short-term administration of multi-strain probiotics effectively reduced the recurrence of respiratory infections in children, particularly among breastfed individuals. These findings support the use of probiotics as a safe, beneficial adjunct in pediatric respiratory infection management.